2008
DOI: 10.1186/1471-2458-8-139
|View full text |Cite
|
Sign up to set email alerts
|

What they fill in today, may not be useful tomorrow: Lessons learned from studying Medical Records at the Women hospital in Tabriz, Iran

Abstract: Background: The medical record is used to document patient's medical history, illnesses and treatment procedures. The information inside is useful when all needed information is documented properly. Medical care providers in Iran have complained of low quality of Medical Records. This study was designed to evaluate the quality of the Medical Records at the university hospital in Tabriz, Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…Because medical records are kept primarily for patient care purposes with secondary uses for billing, research, and legal documentation, researchers using data derived from medical records must be cognizant of these limitations. [50][51][52][53] However, we expect that the outcomes reported here were likely to be recorded in the medical record with a reasonably high degree of accuracy because of their importance to clinical care. Furthermore, our pre-/postdata review analysis indicated that data were initially entered with a high degree of accuracy.…”
Section: Limitationsmentioning
confidence: 99%
“…Because medical records are kept primarily for patient care purposes with secondary uses for billing, research, and legal documentation, researchers using data derived from medical records must be cognizant of these limitations. [50][51][52][53] However, we expect that the outcomes reported here were likely to be recorded in the medical record with a reasonably high degree of accuracy because of their importance to clinical care. Furthermore, our pre-/postdata review analysis indicated that data were initially entered with a high degree of accuracy.…”
Section: Limitationsmentioning
confidence: 99%
“…However, there are a number of challenges affecting hospital data generation, preservation, management, accessibility, and utilization [ 5 – 8 ]. The challenges include use of outdated registers/forms that require the need of constant revision; shortage of well-trained and experienced personnel; lack of planning in storage of inactive records; incompleteness of forms (missing of variables); inadequate storage facilities; and lack of determination of records retention period [ 6 , 7 , 9 ]. These weaknesses are compounded in continued use of paper-based hospital information systems in low-income countries that are prone to damage [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In primary health care (PHC), e-records have uses beyond simply retrieval of patient information; for example, warnings of allergies and drug interactions, developing management protocols for chronic illness, generating pre-appointment reminders and establishing communication links between different levels of care [2,3]. E-records are assumed to improve the quality of documentation over paper-based medical records via automatic reminders to health-care professionals of important data that are missing [4,5]. Some authors, however, have warned that inadequate computer skills or lack of training of health professionals together with limitations in erecords software could result in the data in e-records being truncated compared with paper-based records [6].…”
Section: Introductionmentioning
confidence: 99%